NGHIÊN CỨU ĐẶC ĐIỂM SINH HỌC VÀ KHẢ NĂNG SINH ENZYME NGOẠI BÀO CỦA HAI CHỦNG NẤM MEN SINH BÀO TỬ BẮN THUỘC CHI BULLERA - Đào, Thị Lương (2016)
Thirty nine ballistoconidium-forming yeast strains, isolated from the wilting leaves in Cuc Phuong National Park in Ninh Binh province, Vietnam, were assigned to the genus Bullera based on the colony morphology, the presence of xylose in the cells, of Q-10 as a major ubiquinone and the production of symmetrical bailistoconidia and budding cells. All of these are yeast trains capable of decomposing at least 3 from 5 tested undesirable organic substances as starch, amylase, casein, CMC, chitinase, and lipid. None of these possesses antibacterial substances against pathogenic microorganisms. Among the 39 studied strains, two strains designated as VY-116 and VY-142, showed high amylolytic, chitinolytic, cellulolytic, proteolytic and lipolytic activities. Phylogenetic studies based on the sequence of 26S rDNA (D1/D2) of these strains showed that they might represent 2 new species of the genus Bullera. Research on optimization of cultural conditions for the growth and enzyme production was carried out for these two strains. It showed that these strains best grow and produce enzymes at 20 - 25°C, pH 6 - 7, in the YM medium, after 6 days of fermentation. The optimum condition for enzymatic activities are 40 - 50°C, pH 6 - 7.